Physical geology - Plummer, Charles C. (McGraw-Hill, 2013)
Students taking introductory physical geology to fulfill a science elective, as well as those contemplating a career in geology, will appreciate the accessible writing style and depth of coverage. This book includes numerous chapter learning tools and a website further assist students in their study of physical geology.